2016
DOI: 10.1002/eat.22599
|View full text |Cite
|
Sign up to set email alerts
|

Examination of parental dieting and comments as risk factors for increased drive for thinness in men and women at 20‐year follow‐up

Abstract: While our study supports parental influence on children's eating attitudes, it suggests a need to consider gender and mode of influence. Prevention efforts focused on challenging cultural standards of appearance may benefit from incorporation of parents. © 2016 Wiley Periodicals, Inc.(Int J Eat Disord 2017; 50:490-497).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 46 publications
0
6
0
2
Order By: Relevance
“…For example, a teen exhibiting low health motivation and unhealthy eating habits may perceive they receive more challenging messages and therefore report more negative comments [39]. Klein et al (2017) reported that paternal comments for their all-female cohort (m = 19.87, +/− 1.64), significantly predicted drive for thinness in women 20 years later [40]. Ackard et al (2006) also found that 52.1% of girls (48.6% boys) would talk to their mother "quite a bit" or "very much" more than their father and "the majority reported they could not talk to their father (quite a bit/very much: 24.6% girls, 38% boys)".…”
Section: Parental Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a teen exhibiting low health motivation and unhealthy eating habits may perceive they receive more challenging messages and therefore report more negative comments [39]. Klein et al (2017) reported that paternal comments for their all-female cohort (m = 19.87, +/− 1.64), significantly predicted drive for thinness in women 20 years later [40]. Ackard et al (2006) also found that 52.1% of girls (48.6% boys) would talk to their mother "quite a bit" or "very much" more than their father and "the majority reported they could not talk to their father (quite a bit/very much: 24.6% girls, 38% boys)".…”
Section: Parental Communicationmentioning
confidence: 99%
“…Without asking the parents of the participants included in this study, we will not know if their comments were intended as positive or negative. However, the results offer valuable insight to how maternal and paternal comments are perceived by adolescents within the context that, without an understanding of how words are intended in communication and parent-adolescent connectedness, even a low level of parent teasing can be problematic [12,18,19,32,39,40,49].…”
Section: Strengths and Limitation And Further Researchmentioning
confidence: 99%
“…Cross-sectional research supports this theory, finding positive associations between maternal dieting habits and children’s dieting practices [ 35 , 36 ]. Longitudinal research corroborates these findings, revealing maternal dieting to be a significant predictor of child drive for thinness, in a 20 year follow up study [ 37 ], hence, the need to understand more about maternal disordered eating behaviors and food parenting practices. This is an important and novel finding as the literature is sparse on the relationship between food literacy and coercive feeding, yet our results point to a need to review the importance placed on developing food literacy as a preventive intervention.…”
Section: Discussionmentioning
confidence: 87%
“…Evidências da literatura apontam a mãe como maior modelo de prática de dietas, de insatisfação com o próprio peso/corpo, que pode determinar um maior desejo das filhas pela busca da magreza 25,26 . Cooley et al 27 e Bauer et al 28 apontam que dois mecanismos poderiam explicar o efeito dessas práticas: um em que a mãe encorajaria de forma direta a filha a mudar o peso ou forma e o outro em que a mãe de forma indireta encoraja por meio de seus comentários sobre seu próprio peso e seu comportamento de fazer dieta.…”
Section: Discussionunclassified
“…Cooley et al 27 e Bauer et al 28 apontam que dois mecanismos poderiam explicar o efeito dessas práticas: um em que a mãe encorajaria de forma direta a filha a mudar o peso ou forma e o outro em que a mãe de forma indireta encoraja por meio de seus comentários sobre seu próprio peso e seu comportamento de fazer dieta. Apesar dos autores apontarem esses mecanismos em conjunto como determinantes de maior insatisfação corporal nas filhas, estudos indicam que o incentivo a fazer dieta tem mais efeito no desejo por emagrecer nas filhas do que os comentários sobre o próprio peso da mãe 25,26 .…”
Section: Discussionunclassified